2016
DOI: 10.2485/jhtb.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low-Intensity Pulsed Ultrasound Stimulation on Expression of Bone-Related Genes in Rat Bone Marrow Cells

Abstract: Low-intensity pulsed ultrasound (LIPUS) is used in physiotherapy and bone fracture healing. Previously we demonstrated that LIPUS enhances bone formation around dental implants inserted into rabbit femur. Here, we present the effect of LIPUS treatment on cell proliferation, alkaline phosphatase (ALPase) activity, and the expression of bone-related genes in bone marrow cells. Cell proliferation was not affected by LIPUS treatment. ALPase activity was increased on day 6 after LIPUS treatment in cells treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…This leads to increased gene expression [47,48], which in turn leads to increased protein expression [49]. LIPUS increases RANK-L (receptor activator of nuclear factor kappa-ligand) protein expression in the osteoclasts to accelerate bone resorption [50,51], while in osteoblasts LIPUS increases bone-forming proteins RUNX2 (runt-related transcription factor 2) [52], OPG (osteoprotegerin) [53], and ALP (alkaline phosphatase) [54].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to increased gene expression [47,48], which in turn leads to increased protein expression [49]. LIPUS increases RANK-L (receptor activator of nuclear factor kappa-ligand) protein expression in the osteoclasts to accelerate bone resorption [50,51], while in osteoblasts LIPUS increases bone-forming proteins RUNX2 (runt-related transcription factor 2) [52], OPG (osteoprotegerin) [53], and ALP (alkaline phosphatase) [54].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports suggest that LIPUS does not affect cell proliferation . Akagi et al reported no influence of LIPUS on cell proliferation in rat bone marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports suggest that LIPUS does not affect cell proliferation . Akagi et al reported no influence of LIPUS on cell proliferation in rat bone marrow cells. Veronick et al demonstrated that LIPUS had no effect on MC3T3 mouse osteoblast cell proliferation on hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the cell number on days 5 and 7 did not show any statistical difference between the LIPUS and control groups. Akagi et al also reported that LIPUS had no effect on cell proliferation 34) . In contrast, LIPUS was shown to have a positive effect in the proliferation of osteoblastic cells 39,40) .…”
Section: Cell Proliferationmentioning
confidence: 99%
“…In the orthopedic field, LIPUS has been used to accelerate the process of bone fractures healing [9][10][11] . Although, the biological processes involved in accelerating the repair of the bone fracture when treated with LIPUS are not still fully understood 30) , it was reported that the production of cyclooxygenese 2 (COX-2) in cells was enhanced; this in turn stimulated molecules for enhanced fracture repair 31) through not only increasing the levels of osteogenic molecules, such as bone morphogenetic proteins (BMPs) [32][33][34] , insulin-like growth factor 1 (IGF-1) 35) , stromal cell-derived factor 1 (SDF-1) 36) , and Prostaglandin E2 (PGE2) 37) , but also through promoting the apoptosis of osteoclasts 38) .…”
Section: Treatment With Lipusmentioning
confidence: 99%